Variants in ELL2 influencing immunoglobulin levels associate with multiple myeloma - Swaminathan, Bhairavi; Thorleifsson, Guðmar; Jöud, Magnus; Ali, Mina; Johnsson, Ellinor; Ajore, Ram; Sulem, Patrick; Halvarsson, Britt-Marie; Eyjolfsson, Guðmundur; Haraldsdottir, Vilhelmina; Hultman, Christina; Ingelsson, Erik; et al. (Nature communications, 2015)
Multiple myeloma (MM) is characterized by an uninhibited, clonal growth of plasma cells. While first-degree relatives of patients with MM show an increased risk of MM, the genetic basis of inherited MM susceptibility is incompletely understood. Here we report a genome-wide association study in the Nordic region identifying a novel MM risk locus at ELL2 (rs56219066T; odds ratio (OR)=1.25; P =9.6 × 10 −10 ). This gene encodes a stoichiometrically limiting component of the super-elongation complex that drives secretory-specific immunoglobulin mRNA production and transcriptional regulation in plasma cells. We find that the MM risk allele harbours a Thr298Ala missense variant in an ELL2 domain required for transcription elongation. Consistent with a hypomorphic effect, we find that the MM risk allele also associates with reduced levels of immunoglobulin A (IgA) and G (IgG) in healthy subjects ( P =8.6 × 10 −9 and P =6.4 × 10 −3 , respectively) and, potentially, with an increased risk of bacterial meningitis (OR=1.30; P =0.0024). Multiple myeloma is an incurable and fatal disease characterized by uninhibited growth of plasma cells in the bone marrow. Here, Swaminathan et al. conduct a genome-wide association study and identify a novel risk locus at ELL2 , which encodes a key component of the super-elongation complex.